Genetic Characterization of Fungi Isolated from Environmental Samples: A Molecular Surveillance Study of Public Health Importance. (23rd November 2019) - Sulaiman, Irshad M; Jacobs, Emily; Simpson, Steven B
Abstract: Background: A multistate fungal meningitis outbreak began in September 2012 that affected 751 individuals who received contaminated spinal injections across 20 states in the United States, which led to 64 deaths. In our previous study, we examined 26 environmental swab samples collected from various locations of the manufacturing premises of the compounding company to determine the possible cause of this outbreak and identified 14 novel species of fungi. Objective: In this follow-up study, a total of 198 environmental surveillance samples were collected and analyzed to detect pathogenic fungal species from other compounding company premises located in three regions of the United States. Methods: DNA sequencing was performed at the large subunit ribosomal RNA (LSU rRNA) and internal transcribed spacer (ITS) regions on the 25 positive fungal isolates. Results: Sequence analysis of the ITS1, the ITS2, and the LSU rRNA regions confirmed the presence of the following fungal species in the samples analyzed: ( 1 ) Pestalotiopsis cocculi from the region I; ( 2 ) Epicoccum nigrum and Trichaptum biforme from the region I; ( 3 ) Nigrospora sphaerica and Fusarium sp. from the region II; and ( 4 ) Curvularia sp., Fusarium sp., Penicillium sp., and Preussia sp. from the region III. Conclusions: Our results suggest that the LSU and ITS regions are good genetic markers to perform fungal typing. Highlights: DNA sequencing technology can be used in the implementation of effective environmental monitoring programs of public health importance.